Effect of Preservative Pretreatment on the Biological Durability of Corn Straw Fiber/HDPE Composites - Lihui, Xuan; Dongxue, Hui; Wanli, Cheng; Wong, Andrew H.H; Guangping, Han; Wei, Khong Tan; Tawi, Carlson A.D. (MDPI AG, Basel, Switzerland, 2017)
The effects of alkaline copper quaternary (ACQ) and zinc borate (ZB) on the resistance of corn stalk fiber (CSF)-reinforced high-density polyethylene (HDPE) composites to biodegradation were examined. Both biocides could inhibit termites, mold fungi, and wood-decay fungi, even at high CSF formulations (i.e., 60%). Additionally, ACQ enhanced the resistance of the composite materials to certain biotic stresses better than ZB. The CSF/HDPE composites treated with ACQ at the 3.0% level exhibited a superior performance against termites, white rot fungi, and brown rot fungi. ACQ treatment at the 1% level was optimal for inhibiting soft rot fungi. Furthermore, mold growth was not observed on ACQ-treated CSF/HDPE samples. The untreated CSF/HDPE composites were more susceptible to mold infections and decay than the untreated poplar/HDPE composites, likely because of an incomplete removal of the pith. The chemical features of the corn stalk may also have influenced these differences, but this possibility will need to be explored in future investigations. Furthermore, the CSF component of CSF/HDPE composites is highly susceptible to fungal attacks, with the soft rot fungus inducing the largest mass losses, followed by the white rot fungus, and then the brown rot fungus.